Uso da sedação consciente com óxido nitroso e oxigênio na odontologia - Nazario, Thallita Braga (2020)
Fear and anxiety are present in the dentist’s routine. They are a barrier to the success of dental treatment, a fact that leads to a reduction in the quality of oral health. Thus, the phobia presented by the patient can negatively affect the professional activity, reducing or preventing the execution and quality of the work to be performed. Strategies such greeting and the patient's behavioral management are aspects traditionally applied. However, there is a need for more effective control. Among these, the usage of sedation stands out, either through chemical agents administered orally or inhaled. The present study aims to report a case where the patient was subjected to periodontal treatment and was under conscious sedation by means of nitrous oxide associated with oxygen.